Art Education today: From contemporary dystopias to sustainable societies - Oliveira, Mónica; Sousa, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article aims to identify the challenges that art education faces in initial teacher training and to list the aspects that should guide new pedagogical practices orien- ted towards sustainability. A qualitative research based on a multiple case study, has been chosen through an interview with Higher Education teachers in Portugal and Spain. The conclusions point to the need for a re-foundation of arts education in the light of societal challenges, involving students in the construction of an active citizenship.